Penerapan Filsafat Montessori dalam Pengembangan Kemandirian Siswa Sekolah Dasar Fase A, B, dan C di SDIT Cendekia Purwakarta - Amelia Pratiwi; Wita Puspita Sari; Silvi Madya; Ricky Yoseptry; Wachyudin Wachyudin (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This research is motivated by the understanding that basic education plays a crucial role in forming the foundation of students’ personality, character, and life skills. One important character aspect that must be developed from an early age is independence. This study employs a descriptive qualitative approach. The qualitative method was chosen because the aim is to examine comprehensively and in depth the implementation of educational philosophy in real field contexts. Descriptive research seeks to systematically and accurately describe the facts and characteristics of the object under study. Through this approach, researchers are able to understand the meanings, processes, and experiences of the subjects involved in the implementation of the Montessori approach. The research was conducted at SDIT Cendekia Purwakarta. The research subjects were focused on students in Phase A, B, and C (equivalent to grades 1 through 6). In addition to students, key informants included the school principal, teachers, and parent representatives. Overall, the study concludes that the implementation of Montessori philosophy at SDIT Cendekia Purwakarta is carried out partially yet consistently and has a significant positive influence on the development of children’s independence in Phases A, B, and C. Although the implementation does not fully adhere to pure Montessori standards, the adaptations made produce relevant, measurable outcomes that align with students’ developmental needs. The integration of Montessori values with Islamic values has been proven to be mutually supportive and not contradictory.